Video-Based Feedback To Improve Soccer Passing Technique In Soccer School Students Aged 12-15 Years 12-15 YEARS - Muhammad Sobri Maulana; Dwitia Pratiwi; Arditya Prayogi (Gorontalo State University, 2026)
The development of passing skill in youth soccer requires feedback that is specific, timely, and easy for players to understand. Grassroots soccer schools often rely primarily on verbal correction, whereas low-cost video-based feedback models that combine visual review, technique rubrics, and weekly monitoring remain insufficiently examined in applied Indonesian youth contexts. This pilot quasi-experimental study examined changes in passing accuracy, technical execution, test completion time, and learning motivation after a six-week smartphone-based video feedback program among 30 soccer school players aged 12-15 years. The intervention consisted of video recording from side and rear angles, brief coach feedback, individual reflection, and corrected passing drills. Passing accuracy increased from 59.34 ± 4.78% to 67.28 ± 7.55%, technique scores increased from 62.70 ± 6.37 to 72.90 ± 8.98, completion time decreased from 57.28 ± 3.90 s to 53.01 ± 5.68 s, and motivation scores increased from 3.22 ± 0.57 to 3.65 ± 0.75. Paired-sample tests showed statistically significant pre-post changes with moderate-to-large standardized effects. Because the study used a one-group design, the findings should be interpreted as preliminary associations rather than definitive causal evidence. The main contribution of this study is a practical feedback cycle that integrates smartphone video, an observable technique rubric, and short reflective targets for youth soccer coaching.